2021
DOI: 10.7759/cureus.14530
|View full text |Cite
|
Sign up to set email alerts
|

Admission Cardiotocography as a Predictor of Low Apgar Score: An Observational, Cross-Sectional Study

Abstract: Background and objectiveCardiotocography (CTG) has been used more frequently in recent decades to reduce intrapartum fetal mortality rates. The purpose of this study was to determine whether pathological or non-reactive CTG could predict a low Apgar (Appearance, Pulse, Grimace, Activity, and Respiration) score. An abnormal trace would indicate a distressed fetus, whereas a normal trace would indicate a well-oxygenated fetus. MethodsThis study included a total of 470 women with a gestational period of more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Among risk factors for delivery with grade 2 and 3 MSAF, we confirmed a positive correlation with the duration of labor which is expected considering that the physiopathological mechanisms of MSAF can be favored by its prolongation [26]. Similarly, the correlation between abnormal CTG and development of grade 2 and 3 MSAF confirms the results of previous studies [27,28] and can be explained by the fact that both are expressions of fetal distress. In agreement with Kim et al [29] and Salameh et al [30], we confirmed that epidural analgesia increased the risk of grade 2 and 3 MSAF, but this correlation requires further confirmation because other authors have found conflicting results [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…Among risk factors for delivery with grade 2 and 3 MSAF, we confirmed a positive correlation with the duration of labor which is expected considering that the physiopathological mechanisms of MSAF can be favored by its prolongation [26]. Similarly, the correlation between abnormal CTG and development of grade 2 and 3 MSAF confirms the results of previous studies [27,28] and can be explained by the fact that both are expressions of fetal distress. In agreement with Kim et al [29] and Salameh et al [30], we confirmed that epidural analgesia increased the risk of grade 2 and 3 MSAF, but this correlation requires further confirmation because other authors have found conflicting results [31,32].…”
Section: Discussionsupporting
confidence: 89%
“…Results of our study was comparable to the studies conducted in past. [15,16] Predicting fetal discomfort with cardiotocography in low and high risk pregnancies. Several options exist for dealing with "high risk" women, but there has to be a better way to identify "fetal distress" in "low risk" women [17].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our study Nazir et al where none of the patients with reassuring CTGs had their neonates admitted to NICU. 17 Only two patients out of 470 had babies with an Apgar score below 6, despite a normal CTG trace. This is because they had taken in all antenatal patients while we had included only high-risk patients.…”
Section: Apgar Score At 5 Minutesmentioning
confidence: 94%